2020
DOI: 10.1038/s41598-020-67719-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in food consumption between patients with Hashimoto’s thyroiditis and healthy individuals

Abstract: Food is considered as important environmental factor that plays a role in development of Hashimoto's thyroiditis (HT). The goal of our study was to identify food groups, assessed by food frequency questionnaire, that differ in consumption frequency between 491 patients with HT and 433 controls. We also analysed association of food groups with the wealth of HT-related clinical traits and symptoms. We found significantly increased consumption of animal fat (OR 1.55, p < 0.0001) and processed meat (OR 1.16, p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 66 publications
(66 reference statements)
1
16
1
2
Order By: Relevance
“…There is a lack of comprehensive studies investigating dietary habits and their influence on HT. Only a few studies have analyzed the prevalence of HT concerning dietary habits [ 62 , 138 , 139 , 140 , 141 ]. Moreover, there are still no nutritional guidelines dedicated to HT patients.…”
Section: Diet In Htmentioning
confidence: 99%
“…There is a lack of comprehensive studies investigating dietary habits and their influence on HT. Only a few studies have analyzed the prevalence of HT concerning dietary habits [ 62 , 138 , 139 , 140 , 141 ]. Moreover, there are still no nutritional guidelines dedicated to HT patients.…”
Section: Diet In Htmentioning
confidence: 99%
“…However, TN have been found to be a frequent disease even in those countries and regions where the population is never exposed to I deficiency [4]. Moreover, it was shown that iodine excess has severe effects on human health and associated with the development of thyroidal disfunctions and autoimmunity, nodular and diffuse goiter, benign and malignant tumors of gland [5][6][7][8]. It was also demonstrated that besides the iodine deficiency and excess many other dietary, environmental, and occupational factors are associated with the HT incidence [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The eating patterns of patients with Hashimoto's disease are not fully recognized. It is known that people with this disease consume red meat, fish, dairy products [25], and animal fats [26] more often than healthy foods. Moreover, they are not likely to change their diet after being diagnosed with HT.…”
Section: Introductionmentioning
confidence: 99%